2016
DOI: 10.1111/bjd.14291
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of naevus patterns in an adult twin cohort from the Brisbane Twin Registry: a cross-sectional study

Abstract: This study strongly supports a heritable component to TNC, as well as changes in TNC, and the number of medium-sized naevi, light-brown naevi, specific sites and certain dermoscopic features in adults. These characteristics should be taken into account by naevus surveillance programmes and further studied to identify candidate gene associations for clinical and dermoscopic patterns in conjunction with melanoma risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Melanocytic naevi remain clinically dynamic throughout an individual's life, with increasing numbers as one approaches middle age and regression in the later decades of life . Additionally, total body naevus count has been shown to be a highly heritable trait; our results, which include 57 twin pairs, show that iris pigmented lesion count is as heritable (Table S3; see Supporting Information) as body naevus count, at 72%. This is consistent with our findings that OCA2 and IRF4 are major contributors to the phenotype.…”
Section: Discussionmentioning
confidence: 65%
“…Melanocytic naevi remain clinically dynamic throughout an individual's life, with increasing numbers as one approaches middle age and regression in the later decades of life . Additionally, total body naevus count has been shown to be a highly heritable trait; our results, which include 57 twin pairs, show that iris pigmented lesion count is as heritable (Table S3; see Supporting Information) as body naevus count, at 72%. This is consistent with our findings that OCA2 and IRF4 are major contributors to the phenotype.…”
Section: Discussionmentioning
confidence: 65%
“…Secondly, the study by Lee et al . showed that, for sun‐exposed sites, intraclass correlations were higher in MZ than in DZ twins, with a high heritability, suggesting the importance of the interaction of genes and environmental factors . Thirdly, there were also significant differences between MZ and DZ twins with regard to the upper and lower limbs (heritabilities of 98% and 64%, respectively), which are sun‐exposed body sites.…”
mentioning
confidence: 94%
“…The main findings of the study by Lee et al . shed new light on the heritability of naevus pattern, with a special emphasis on TNC, sun‐exposed areas and dermoscopic pattern . Theoretically, these data will have an impact on current screening and monitoring strategies for the detection of melanoma.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The risk of developing naevi is, in turn, modulated by environmental, phenotypic and genetic factors. The presence of naevi is a phenotypic trait under strong genetic control [64].…”
Section: Naevi As a Risk Factor For Melanomamentioning
confidence: 99%